Sixty-one day twin to twin birth interval in a low technology setting (2002)
Multiple pregnancy, whether spontaneous or from artificial reproductive techniques, is regarded us high risk. Limiting the twin-twin birth interval to within 30 minutes has been widely practised. However, conservative management of the retained live, immature second twin may be worthwhile. We report a case lasting sixty-one days in a low technology setting.